TREATMENT OF GIANT JUVENILE FIBROADENOMA: RESULT AFTER MINIMALLY INVASIVE APPROACH WITHOUT RECONSTRUCTIVE SURGERY - Lima, Cátia Cilene Aires; Lima, Renilton Aires (Mastology, 2018)
Fibroadenomas are common benign tumors of the female breast. Those that present as rapidly growing breast tumors exceeding 5 cm in diameter or 500 g in weight in young female patients are commonly classified as giant juvenile fibroadenomas. These tumors are rare, and due to their excessive growth, they are usually enucleated to clarify a malignant origin, to differentiate from phyllodes tumor and to prevent persisting deformities of the breast. This report details the surgical approach to this clinical problem in a 14-year-old female with functional preservation of the breast and a good esthetic result.